If Life Throws You Lemons, Try To Make Lemonade: Does Locus of Control Help People Cope with Unexpected Shocks? - Stillman, S; Velamuri, M; Stillman, Steven; Velamuri, Malathi (Institute for the Study of Labor (IZA), 2016)
A number of recent papers have found that non-cognitive skills and in particular, locus of control (LoC), are important predictors of success in life in terms of both traditional labor market and socioeconomic outcomes, and measures of subjective wellbeing. Specifically, the literature has found a strong correlation between having an internal locus of control and standard measures of success and happiness. In this paper, we examine whether having an internal LoC also helps people manage the consequences of two mainly unanticipated negative shocks, being a crime victim and experiencing a serious illness or injury. We find that these events have large negative consequences on both subjective wellbeing and objective economic outcomes. For men, these shocks have smaller effects on subjective wellbeing when they are more internal but that the long-run effects on income are no smaller. On the other hand, for women with an internal LoC, we find some evidence that these shocks have larger impacts. We draw on the psychology literature to discuss the results.
IZA Discussion Paper No. 10210
Keywords: Health -- Injury; Life Events; Stress; Disadvantage, adversity and resilience; Health and wellbeing; Health; Stress; Life Events; Injury; Adversity and resilience; Dsiadvantage, adversity and resilience; Health and wellbeing